Retratos de relações de gênero em catálogos de brinquedos - Kropeniscki, Fernanda Battagli (2015)
Toys, industrialized or not, are part of the world of children. A simple object can be transformed into toy in the course of play, as the imagination of every child. However, to pay attention to industrialized toys, we face not only their material image, they also recorded the images that manufacturers have of themselves and children. Certainly, offered toys follow the dictates of culture, to be accepted and purchased by consumers. Thus, to go toys catalogs, we came across a direction of play of girls and boys, since our culture is marked by a binary model of gender. The gender difference performed even before a child is born is responsible for different education of girls and boys. In this process, alternative femininity and masculinity are marginalized, they become prejudices target. The present dissertation aimed to discuss gender relations which are in toy catalogs of a factory in southern Brazil, from 2009 to 2015. Considering the changes that have already occurred in gender relations in our society, we tried to look at what had already been changing in the production and supply of toys. Household items and plug-in blocks characterize most of the products offered. During the covered period, it was observed some changes, especially in gender indication presented with the toys. The plug-in blocks, with predominant theme of car racing, wars, public safety, works in the city, transport means and robots, are offered at first only for boys. Already household items, initially indicated only for girls, they enter gradually the male territory. It is only from the 2013 catalog that all toys are now given for girls and boys. But what does it represent? A broadening of possibilities for the play of children and at the same time, a camouflaged binary. Colors, designs and themes are held. To the boys are already "allowed" the female environment, and, likewise, the girls are already "authorized" to go the male environment. In this scenario, you can see a demarcation of the female and male. However, some launches bring other changes analyzable. The plug-in blocks now earn new colors and allow other stories, with pink and purple composing scenarios considered feminine. Similarly, in 2015, part of the kitchen is posted out of the traditional combination of pink, white and purple, now brings "neutral" colors, more inviting to the boys. Finally, it is considered that the supply of toys is already blurring their gender boundaries. But changes do not occur suddenly, seeing that, among many regulatory mechanisms, the supply of toys is just one of them.